Unraveling Heterogeneity of Tumor Cells and Microenvironment and Its Clinical Implications for Triple Negative Breast Cancer - Jiang, Ke; Dong, Mengting; Li, Chunyang; Sheng, Jiayu (Frontiers in Oncology, 2021)
Objective: Triple negative breast cancer (TNBC) is an aggressive subtype of breast cancer, characterized by extensive intratumoral heterogeneity. We aimed to systematically characterize the tumor heterogeneity of TNBC. Methods: Single-cell RNA sequencing (scRNA-seq) of TNBC cells were obtained from the GSE118389 and GSE75688 datasets. After integration of the two datasets, cell clustering analysis was performed using the Seurat package. According to the marker genes of cell cycle, cell cycle of each cell cluster was determined. Then, function enrichment analysis of marker genes in each cell cluster was performed, followed by ligand–receptor signaling network analysis. CIBERSORT was used to estimate the proportion of 22 immune cells in each sample based on RNA-seq data of 58 normal adjacent tissues and 101 TNBC tissues. After that, prognostic value of immune cells was assessed. Results: In the integrated datasets, five cells types including B cells, myeloid cells, stromal cells, T cells, and tumor cells were clustered. Functional enrichment analysis revealed the functional heterogeneity of genes in each cell. Intercellular communication networks were conducted based on ligand–receptor pairs. The heterogeneity in the fractions of 22 immune cells was found in TNBC tissues. Furthermore, there was a significant difference in the fractions of these immune cells between adjacent normal tissues and TNBC tissues. Among them, M2 macrophages and neutrophils were significantly associated with clinical outcomes of TNBC. Moreover, the fractions of T cells CD4 memory resting, monocytes, neutrophils, M1 macrophages, and T cells CD4 memory activated were significantly correlated with clinical characteristics of TNBC. As shown in PCA results, these immune cells could significantly distinguish TNBC tissues into adjacent normal tissues. Conclusion: Our findings characterized the tumor heterogeneity of TNBC, which deepened the understanding of the complex interactions between tumor cells and their microenvironment, especially immune cells.